The Analysis of the Translation Surah Al-Fatihah in the Rhymed Free Translation of the Quran in the Acehnese Language - Rahil Helmi; Wita Dwi Payana (Prologue: Journal on Language and Literature, 2023)
This research aims to comprehend the meaning contained in the free verse translation of the Acehnese language Quran in Surah Al-Fatihah. The method used in this research is qualitative descriptive research. The data is analysed using introspection method because the researcher is a native speaker of Acehnese. Introspection method is a way to obtain data by using the language intuition of someone who learns the original language, to provide the necessary data for analysis according to the research objectives. The results obtained in this study indicate that Surah Al-Fatihah is an opening chapter that holds significant meaning as the preface to the recitation of the entire verses of the Quran. In the process of translating these verses, a deep understanding of the linguistic complexity of the Acehnese language itself is required. The translation of Surah Al-Fatihah into Acehnese adds a cultural and linguistic dimension to the experience of reading the Quran for Acehnese speakers. This allows the speakers to feel more connected to the text on a profound level. With the existence of a free verse translation of the Quran in Acehnese, a path is paved or an opportunity is opened to strengthen the Acehnese language with all its attributes